Empowerment and Counseling about Traditional Medicinal Plants (Jamu) to Facilitate Breast Milk (ASI) for Breastfeeding Mothers and PKK Mothers in Pasar X Village, Kutalimbaru District - Betty Mangkuji; Jujuren Br Sitepu; Arihta Br Sembiring (Jurnal Pengabdian Masyarakat Bestari, 2023)
This community service activity aims to increase the knowledge and skills of mothers with babies aged 0-2 years, PKK mothers and cadre mothers to better understand the benefits of herbal medicine and how to make and distribute leaflets on ingredients for making herbal medicine and it is hoped that respondents will practice it at home. The community service method involves providing outreach on the benefits of breast milk for babies, the benefits of herbal medicine as well as herbal medicine ingredients and how to make it through lectures, discussions and demonstrations of making herbal medicine. And the counseling was evaluated with pre-tests and post-tests, distribution of leafeads and the practice of making herbal medicine which was carried out at the Siti Rohana Br Ginting clinic as a midwife in Pasar X village, Kutalimbaru sub-district. The results obtained after carrying out community service regarding the benefits of herbal medicine, knowledge about the benefits of herbal medicine increased from 65% who did not know to 87%. And from 81.6% who did not know the ingredients and how to make it and after being given an explanation the ingredients and how to make it increased to 91.1%. Suggestions for village midwives and posyandu cadres to explain the benefits of herbal medicine and ingredients to breastfeeding mothers. Use leafheads so that the culture is not lost.